Manusia dan Alam Sekitar: Hubungannya daripada Perspektif Islam - Ghazali, Amer Saifude (Jurnal Usuluddin, 1997)
Man and environment are two main elements in nature. It’s has been said that the tremendous growth of human population especially in the Third World contributes significantly to the environmental crisis. Based on this assumption. International Conference of People and Development (ICPD) held in Egypt on 1994 proposed a mechanism to prevent the population growth in the Third World. It is true that the population growth directly related to the environmental crisis’ This article tries to examine the relationship between man and environment from an Islamic perspective and the option we have to harmonise this relationship.